Psychological and pedagogical bases for determining the content and structure of pedagogical test (Pedagogy of Higher and Secondary Education, 2012)
Pyeychyeva L. D. Psychological and pedagogical bases for determining the content and structure of pedagogical test.The article is dedicated to the generalization of the main psychopedagogical approaches to the determination of the pedagogical test content and structure. The classification of test questions main types as a test structural unit is supplied. The merits and demerits of test questions and also formal, statistical and psycho-pedagogical requirements for their inclusion to the pedagogical test content are considered.
Keywords: pedagogical test; test-like questions; test question; essay question; objective question